Comparison of the next-generation aminoglycoside plazomicin to gentamicin, tobramycin and amikacin. Issue 4 (2012) - Zhanel, George G; Lawson, Christopher D; Zelenitsky, Sheryl; Findlay, Brandon; Schweizer, Frank; Adam, Heather; Walkty, Andrew; Rubinstein, Ethan; Gin, Alfred S; Hoban, Daryl J; Lynch, Joseph P; Karlowsky, James A
Plazomicin (formerly ACHN-490) is a next-generation aminoglycoside that was synthetically derived from sisomicin by appending a hydroxy-aminobutyric acid substituent at position 1 and a hydroxyethyl substituent at position 6′. Plazomicin inhibits bacterial protein synthesis and exhibits dose-dependent bactericidal activity. Plazomicin demonstrates activity against both Gram-negative and Gram-positive bacterial pathogens, including isolates harboring any of the clinically relevant aminoglycoside-modifying enzymes. However, like older parenteral aminoglycosides, plazomicin is not active against bacterial isolates expressing ribosomal methyltransferases conferring aminoglycoside resistance. Plazomicin has been reported to demonstrate in vitro synergistic activity when combined with daptomycin or ceftobiprole versus methicillin-resistant Staphylococcus aureus, heteroresistant vancomycin-intermediate S. aureus, vancomycin-intermediate S. aureus, and vancomycin-resistant S. aureus and against Pseudomonas aeruginosa when combined with cefepime, doripenem, imipenem or piperacillin-tazobactam. After intravenous administration of plazomicin to humans at a dose of 15 mg/ kg, the maximum concentraration was 113 μg/ml, the area under the curve0–24 was 239 h·μg/ml, the half-life was 4.0 h and the steady-state volume of distribution was 0.24 L/kg. Results from a Phase II randomized, double-blind study in patients with complicated urinary tract infection and acute pyelonephritis including cases with concurrent bacteremia comparing plazomicin 15 mg/kg intravenously once daily for 5 days with levofloxacin 750 mg intravenously. for 5 days are anticipated in 2012. Human studies to date have not reported nephrotoxicity or ototoxicity, and lack of ototoxicity has been reported in the guinea pig model. Given reported increases in bacterial resistance to current antimicrobial agents and the lack of availability of new agents with novel mechanisms, plazomicin may become a welcomed addition to the antibacterial armamentarium pending positive results from large-scale clinical trials and other required clinical studies.